Effect of Organic Fertilizer application rate and Azospirillum brasilense inoculum level on growth and growth components of sweetpotato (Ipomoea batatas L). - M. A., Yassin; Hassan, G. A. El; M. M., Alsamowal; Hadad, M.A. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
A pot experiment was conducted in the green house facility of the College of Agricultural Studies, Sudan University of Science and Technology Shambat, to study the effect of Organic fertilizer application rate and Azospirillum brasilense inoculation on growth and growth components of, sweetpotato (Ipomoea batatas L). Three levels of Azospirillum brasilense inoculum applied were; (0, 104 and 108Cfu/ml), respectively and the three rates of Al Khaseeb Organic fertilizer were; (0 t/ha, 25 t/ha and 50 t/ha). The experiment was set in factorial arrangement in a completely randomized design. Shoot fresh weight and root length showed significant effect with (26.70 g) and (41.33cm) compared to (3.67g) and (16.67 cm) for uninoculated control. However, the shoot dry weight showed a significant effect with (5.10g) compared to (1.3g) for uninoculated control. The results indicated a great potential of using Organic fertilizers and biofertilizers to improve growth and yield of sweetpotato in addition toproduction cost reduction and conservation of natural resources.